REVIEW PENANGANAN KIPI (KEJADIAN IKUTAN PASCA IMUNISASI) DI SDN PETEMON 1 - Ulva Noviana; M. Hasinuddin (STIKES NGUDIA HUSADA MADURA, 2019)
Immunization is an effort to provide immunity to infants and children by inserting vaccines into the body so that the body makes anti-substances to prevent certain diseases (Hidayat, 2008). Meanwhile, Post-Immunization Follow-Up Events (AEFI) is a series of reactions, usually in the form of inflammation in the body, after immunization. Based on the WHO report (Global Immunization Data) in 2010, 1.5 million children died from diseases that can be prevented by immunization and nearly 17% of deaths in children <5 years old can be prevented by immunization. According to Basic Health Research Data in 2013, in Indonesia there were 33.4% of children who had AEFI from 91.3% of the children who received immunizations, namely with symptoms of 20.6% redness, 20.2% swelling, 6.8% high fever. and 6% fester. Based on a survey through interviews with parents of students at SD Petemon 1 that had been conducted, it was found that many parents of SD Petemon 1 students still did not know about the handling of AEFIs. Participants in the activity were 15 parents of students and 10 teachers of SD Petemon 1 who took part in immunization counseling activities, training on handling Post-Immunization Associations (AEFI). During the activity, all participants were very enthusiastic about the material presented. The results of the activity showed an increase in the ability of parents of students and teachers before and after being given immunization counseling and training in handling AEFIs. Before being given training, the knowledge of mothers in the moderate category was 40% and the poor category was 40%. After being given training, knowledge of mothers in the good category was 72%.